2021
DOI: 10.1080/21870764.2021.1911059
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the magnetic properties of M-type strontium ferrite with synergistic effect of co-substitution and calcinations temperature

Abstract: SrFe 12 O 19 samples were initially prepared using sol-gel auto-combustion method and calcined from 500 to 1100°C (for 6 h). XRD data established the phase formation temperature of SrM phase to be ≈1000°C. Thereafter, the effect of Zn 2+ -Zr 4+ co-dopant on magnetic and structural properties of SrZn x Zr x Fe 12-2x O 19 (x = 0.00-1.00) samples calcined between 900-1100°C was investigated. XRD data shows that the cell volume increases (from 690.45Å 3 (x = 0.00) to 705.72Å 3 (x = 1.00)) while crystallite size de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In several investigations that have studied the effect of heat treatment temperature on the crystal structure, size, and physical properties of nanoparticles, it has been reported that the crystallinity of nanometric particles synthesized using methods such as coprecipitation or sol-gel improves as the heat treatment temperature increases 36,37 . Generally, as-synthesized nanoparticles have been found to exhibit low crystallinity 38,39 . To obtain pure Ni-Co mixed ferrite nanocrystals, the powders synthesized using both methods were calcined at 600 °C for 2 hours in an air atmosphere.…”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…In several investigations that have studied the effect of heat treatment temperature on the crystal structure, size, and physical properties of nanoparticles, it has been reported that the crystallinity of nanometric particles synthesized using methods such as coprecipitation or sol-gel improves as the heat treatment temperature increases 36,37 . Generally, as-synthesized nanoparticles have been found to exhibit low crystallinity 38,39 . To obtain pure Ni-Co mixed ferrite nanocrystals, the powders synthesized using both methods were calcined at 600 °C for 2 hours in an air atmosphere.…”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Nanoparticles annealed at 1,000°C possess a uniform hexagonal shape with narrower particle size distribution hence narrow size distribution leads to lower porosity [55]. When particles are annealed at 1,300°C the nanoparticles illustrate an increase in the average grain sizes with calcination temperature due to the fusion of smaller grains into larger grains [56][57][58]. Particle size distribution was shown in Figure 3 for nanoparticles annealed at 1,000 and 1,300°C.…”
Section: Field-emission Scanning Electronmentioning
confidence: 99%
“…A material must have a high reflection loss (RL) and a broad frequency range in order to be used as a microwave absorber. Attenuation of microwaves is affected by the magnetic loss [4], material coercivity [5,6], and dielectric loss [7].…”
Section: Introductionmentioning
confidence: 99%